A biomarker of collagen type I degradation is associated with cardiovascular events and mortality in patients with atherosclerosis. (28th August 2018) - Holm Nielsen, S.; Tengryd, C.; Edsfeldt, A.; Brix, S.; Genovese, F.; Bengtsson, E.; Karsdal, M.; Leeming, D. J.; Nilsson, J.; Goncalves, I.
Abstract: Objective: Atherosclerosis is characterized by accumulation of lipids, cells and extracellular matrix (ECM) proteins in the arterial wall. Collagen type I (COL1), a component of the arterial ECM, is cleaved by matrix metalloproteinases (MMPs) and known to be remodelled in atherosclerosis. We explored whether the MMP‐mediated COL1 biomarker, C1M, was associated with cardiovascular events, cardiovascular mortality and all‐cause mortality in a large prospective cohort of patients with known atherosclerosis. Methods: Serum from 787 patients who underwent a carotid endarterectomy was included. Circulating levels of C1M were measured in serum. A total of 473 patients were followed for 6 years after surgery. Associations between C1M and incidence of cardiovascular events, cardiovascular mortality and all‐cause mortality were assessed by Kaplan–Meier curves and Cox regression analysis. Results: A total of 101 (21.4%) patients suffered from nonfatal cardiovascular events during the follow‐up period, and 64 (13.5%) patients died. Of these, 39 (60.9%) died from cardiovascular diseases. Patients with C1M levels above the median were significantly associated with cardiovascular events, cardiovascular mortality and all‐cause mortality ( P < 0.001, P = 0.004 and P < 0.001, respectively). C1M was included in the final model for prediction of cardiovascular events (HR 2.15, 95% CI 1.40–3.32, P = 0.001), cardiovascular mortality (HR 2.20, 95% CI 1.07–4.51, P = 0.031) and all‐cause mortality (HR 2.98 95% CI 1.67–5.33, P = < 0.001). Conclusions: In patients with atherosclerotic carotid lesions, high levels of C1M predicted cardiovascular events, cardiovascular mortality and all‐cause mortality. These findings emphasize the importance of remodelling mechanisms in atherosclerosis that are now becoming more and more explored.